A computerized and innovative tool to guide interdisciplinary assessment: Exploring the feasibility of the implementation of the Competency Assessment Tool (CAT). (2nd July 2020) - Giroux, Dominique; Vallée, Catherine; Provencher, Véronique; Delli Colli, Nathalie; Poulin, Valérie; Giguère, Anik; Careau, Emmanuelle; Durand, Pierre J.; Carignan, Maude
ABSTRACT: An electronic tool, the Competency Assessment Tool (CAT), was developed in order to guide interdisciplinary teams through clinical competency assessment. Objectives: To support the implementation and perpetuation of the CAT, the objectives were: 1) document health and social service professionals' needs in order to support the use of the CAT; 2) identify the facilitating factors and those hindering the implementation of the CAT in a healthcare establishment; 3) identify strategies favoring the use of the CAT. Participants: Health and social service professionals and doctors were recruited. Methods: A qualitative study was realized by conducting focus groups with health and social service professionals and individual interviews with doctors. Results: The results allowed us to bring to light the CAT's advantages, the issues associated with its implementation (facilitators and obstacles) and the needs to support its use. A number of avenues of intervention were identified and could be put in place to encourage the use of the CAT. Conclusion: This study will support the implementation of the CAT and ultimately, this will allow for the assurance that the decisions taken on the need for protection of vulnerable individuals will be just, rigorous and the fruit of a concerted ethical reflection.